Characterization of the onset of leptin effects on the regulation of energy balance. Issue 3 (2nd June 2021) - Teixeira, Pryscila D S; Ramos-Lobo, Angela M; Rosolen Tavares, Mariana; Wasinski, Frederick; Frazao, Renata; Donato Jr, Jose
Abstract : Leptin is a hormone required for the regulation of body weight in adult animals. However, during the postnatal period, leptin is mostly involved in developmental processes. Because the precise moment at which leptin starts to exert its metabolic effects is not well characterized, our objective was to identify the approximate onset of leptin effects on the regulation of energy balance. We observed that male Lep ob/ob mice started to exhibit increased body fat mass from postnatal day 13 (P13), whereas in females, the increase in adiposity began on P20. Daily leptin injections from P10 to P22 did not reduce the weight gain of WT mice. However, an acute leptin injection induced an anorexigenic response in 10-day-old C57BL/6 mice but not in 7-day-old mice. An age-dependent increase in the number of leptin receptor-expressing neurons and leptin-induced pSTAT3 cells was observed in the hypothalamus of P7, P10 and P16 mice. Leptin deficiency started to modulate the hypothalamic expression of transcripts involved in the regulation of metabolism between P7 and P12. Additionally, fasting-induced hypothalamic responses were prevented by leptin replacement in 10-day-old mice. Finally, 12-day-old males and females showed similar developmental timing of axonal projections of arcuate nucleus neurons in both WT and Lep ob/ob mice. In summary, we provided a detailed characterization of the onset of leptin's effects on the regulation of energy balance. These findings contribute to the understanding of leptin functions during development.